COMMUNITY EMPOWERMENT THROUGH NUTRITION EDUCATION: THE ROLE OF EGG CONSUMPTION IN PREVENTING STUNTING IN KAMPUNG MEYES, NORTH MANOKWARI - Aluisius Widodo; Sri Hartini; Hanike Monim; Dwi Djoko Rahardjo; Elfira K. Suawa; Sangle Y. Randa; Frandz R. Pawere; Johan F. Koibur (Jurnal Abdisci, 2026)
Abstract: Background. Stunting is a chronic form of malnutrition resulting in children being shorter than their age due to prolonged nutrient deficiency and frequent infections. It often begins before birth and continues through early childhood, caused by a lack of essential nutrients such as protein, iron, zinc, and vitamins. Eggs, as an affordable and highly nutritious source of animal protein, are recommended to help prevent stunting in vulnerable communities. Aim. To increase the knowledge and awareness of the Kampung Meyes community about stunting and the importance of consuming eggs, as well as to provide practical education on safe egg preparation for pregnant women, breastfeeding mothers, and toddlers. Methods. The activity was conducted on May 12, 2025, in North Manokwari District, involving 40 participants through leaflet distribution, interactive discussions, and egg provision. Results. The program received enthusiastic responses from children, parents, and community leaders, confirming that combining nutrition education with direct interventions effectively improves understanding and supports national stunting reduction efforts. Conclusions. The results highlight the effectiveness of culturally relevant, action-based learning and suggest the need for continued community guidance. Implication. Integrating this educational model into local health posts, schools, and family welfare groups could ensure sustainable improvements in nutrition and family food security.